2019
DOI: 10.1177/2055207619858564
|View full text |Cite
|
Sign up to set email alerts
|

Use of Amulet in behavioral change for geriatric obesity management

Abstract: Background Obesity in older adults is a significant public health concern. Weight-loss interventions are known to improve physical function but risk the development of sarcopenia. Mobile health devices have the potential to augment existing interventions and, if designed accordingly, could improve one’s physical activity and strength in routine physical activity interventions. Methods and results We present Amulet, a mobile health device that has the capability of engag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Commercial products are starting to move beyond watches into jewellerylike monitors, such as the Ōura ring, 6 the BellaBeat Leaf, 7 and the Kerv Ring. 8 A number of specialised devices have been explored for healthcare use, such as glasses for mental health monitoring (Vidal et al, 2012), wrist-worn devices to engage patients in physical activity (Batsis et al, 2019), a bracelet as visualisation for multiple applications (Fortmann et al, 2016), up to 'soft' IoT devices that aim to blend with the "wearer's personality" (Møller & Kettley, 2017). The typical options that are explored are accessories (such as head-mounted or wrist-worn devices), sensor patches, or eTextiles (Seneviratne et al, 2017).…”
Section: Wearables For Health Monitoringmentioning
confidence: 99%
“…Commercial products are starting to move beyond watches into jewellerylike monitors, such as the Ōura ring, 6 the BellaBeat Leaf, 7 and the Kerv Ring. 8 A number of specialised devices have been explored for healthcare use, such as glasses for mental health monitoring (Vidal et al, 2012), wrist-worn devices to engage patients in physical activity (Batsis et al, 2019), a bracelet as visualisation for multiple applications (Fortmann et al, 2016), up to 'soft' IoT devices that aim to blend with the "wearer's personality" (Møller & Kettley, 2017). The typical options that are explored are accessories (such as head-mounted or wrist-worn devices), sensor patches, or eTextiles (Seneviratne et al, 2017).…”
Section: Wearables For Health Monitoringmentioning
confidence: 99%
“…Self-monitoring is a technology used to provide the elderly with the measurements and early warnings of various physical health indicators, and enable elderly to be at home safely. The authors-Reeder, McManus, Quinn, Willard, Hermanns, et al showed that self-monitoring can be realized in the form of medication-dispensing devices, embedded sensors, self-management applications, wearable systems, online community care platforms, and physical activity trackers [8,9,11,[15][16][17]. In their study, Reeder et al found that home-based devices for medication management and health monitoring can automatically distribute pre-installed drugs and send an alarm to individuals about the medication time.…”
Section: Self-monitoringmentioning
confidence: 99%
“…The study of Batsis, Zaslavsky, and Zhang et al confirmed that smart wearable devices, as cutting-edge technology, play an essential role in self-monitoring technology used in monitoring individual indicators. Specifically, these devices can record data to classify an individual's activity level [17], record sleep data [18], and monitor blood pressure using a wearable blood pressure monitor [19], and ultimately improve the health level of the user.…”
Section: Self-monitoringmentioning
confidence: 99%
See 1 more Smart Citation